PENGARUH INVESTASI SWASTA DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Hari, Kadek Visala; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 7 (2021): VOL 10 NO 7, JULI 2021 [2661 - 3103], 2021)
Social welfare is one of the goals from Sustainable Development Goals . Inequality still occurs of province Bali, especially in the Sargabita area with regions outside it. The objectives of this study are (1) Analyz of private investment and capital expenditure on economic growth in Bali Province. (2) Analyz of private investment, capital expenditure and economic growth on social welfare in Bali Province. (3) Determine whether economic growth mediates effect of investment and capital expenditure on the social welfare in Bali Province. The used are secondary data, with 45 observation. The analysis technique is path analysis. The results of the study (1) Private investment no effect of economic growth but has a positive related, spending capital expenditure has a positive and significant on the economic growth of Bali Province (2) Private investment, capital expenditure and economic growth directly have a positive and significant effect on the welfare of Bali Province. (3) Economic growth is an intervening variable the influence of capital expenditure on community welfare, economic growth is not an intervening variable the effect of private investment on the welfare  of Bali Province.   Keywords: private investment, capital expenditure, economic growth, social welfare